Pengaruh Pendekatan Realistic Mathematic Education Berbantuan Video Animasi Terhadap Minat dan Hasil Belajar Pecahan di Kelas V Sekolah Dasar - Rosihan Anwar; Syafri Ahmad; Melva Zainil; Salmaini Salmaini (Universitas Negeri Padang, 2025)
The background of this study is the low interest and learning outcomes caused by conventional learning, which lacks media and directly presents fractions at the symbolic stage (formulas). The research method used was a quasi-experiment with a non-equivalent control group design. The sampling technique used was purposive sampling, in which the sample was determined non-randomly with the criteria that both classes had comparable characteristics and initial ability levels. This study involved 18 students as the experimental class (RME approach assisted by animated videos) and 16 students as the control class (conventional approach assisted by image media). Data were collected through learning interest questionnaires and learning outcome tests (pre-test and post-test). The results of the study show that the treatment in the experimental class was significantly superior. In terms of learning outcomes, there was an increase in the average score of the experimental class from 58.11 to 85.83, surpassing the control class, which only increased from 58.31 to 76.81. A more striking increase was seen in learning interest, where the percentage of students in the “very high” category in the experimental class jumped from 5.6% to 83.3%. The results of statistical tests using the Independent Sample T-Test and F-Test showed a significance value of 0.037 < 0.05, thus proving the significant effect of the application of video animation-assisted RME. It was concluded that this approach was very effective in increasing students' interest and learning outcomes in mathematics on the subject of fractions.